2004
DOI: 10.2151/jmsj.82.1679
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Re-greening the Desertified Lands in Northwestern China: Implications from a Regional Climate Model Experiment

Abstract: This paper describes a study that investigates the local and regional effects of vegetation restoration in northern China via regional climate model simulations, and reports implications for the sustainability of vegetation under the altered rainfall regime. Ensemble simulations with the current vegetation cover and an idealized re-greening scenario for a test area in northwestern China (90 -110 E and 36 -42 N) were performed using large scale boundary forcing derived from 1998. The results indicate that suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…A number of recent studies have shown that the arid and semiarid areas in northern China have diminished during the last 20 years due largely to land management and afforestation (e.g., Piao et al 2005;Xue et al 2005), which, however, is in contrast to the strengthened anthropogenic activities (such as enhanced grazing and increased population) during the same period (Wang et al 2006b). Furthermore, since the rehabilitated areas are small compared to the existing areas of semiarid regions and sandy lands, it deems to be dubious whether the local to regional changes in the atmospheric circulation and rainfall distribution due to the vegetation restoration could be favorable for the maintenance of the rehabilitated areas (Zheng et al 2002;Sen et al 2004). Sen et al (2004) demonstrated in an idealized numerical simulation that even relatively large re-greening in northern China might be vulnerable without abundant water resources or intensive irrigation because vegetation reclamation would produce more intense precipitation rather than more frequent rainfall that is more appropriate to maintaining the rehabilitated areas.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies have shown that the arid and semiarid areas in northern China have diminished during the last 20 years due largely to land management and afforestation (e.g., Piao et al 2005;Xue et al 2005), which, however, is in contrast to the strengthened anthropogenic activities (such as enhanced grazing and increased population) during the same period (Wang et al 2006b). Furthermore, since the rehabilitated areas are small compared to the existing areas of semiarid regions and sandy lands, it deems to be dubious whether the local to regional changes in the atmospheric circulation and rainfall distribution due to the vegetation restoration could be favorable for the maintenance of the rehabilitated areas (Zheng et al 2002;Sen et al 2004). Sen et al (2004) demonstrated in an idealized numerical simulation that even relatively large re-greening in northern China might be vulnerable without abundant water resources or intensive irrigation because vegetation reclamation would produce more intense precipitation rather than more frequent rainfall that is more appropriate to maintaining the rehabilitated areas.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Furthermore, since the rehabilitated areas are small compared to the existing areas of semiarid regions and sandy lands, it deems to be dubious whether the local to regional changes in the atmospheric circulation and rainfall distribution due to the vegetation restoration could be favorable for the maintenance of the rehabilitated areas (Zheng et al 2002;Sen et al 2004). Sen et al (2004) demonstrated in an idealized numerical simulation that even relatively large re-greening in northern China might be vulnerable without abundant water resources or intensive irrigation because vegetation reclamation would produce more intense precipitation rather than more frequent rainfall that is more appropriate to maintaining the rehabilitated areas.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…6). In another study, Sen et al (2004b) investigated the local and regional effects of vegetation restoration in northern China (90 -110 E, 36 -42 N) using the same RCM, and evaluated whether the changes in rainfall induced by landscape change are large enough to support a restored vegetation cover. Different from other works mentioned above, the studies of Sen et al (2004a,b) took advantage of ensemble simulations to remove the chaotic noise in the simulations, and performed a significance check for the corresponding response to the land use change.…”
Section: Topographic Effects On Regional Climatementioning
confidence: 99%
“…McGregor 1997; Wang et al 2004) and climate sensitivity studies (e.g. Messager et al 2004;Martinez-Castro et al 2006;Sen et al 2004a, b;Bozkurt and Sen 2011).…”
Section: Introductionmentioning
confidence: 99%